Optimizing metal 3D printing powders - Chan, You Ting (Nanyang Technological University, 2024)
This research paper explores the possible optimization of metallic 3D printing powders using Duplex Stainless Steel (DSS) as an example and the associated process parameters. Unlike the traditional subtractive methods in which material is removed to form an object, AM uses additive processes to layer material and result in improved product efficiency and material management. Under consideration here is the manufacturing by means of the Direct Energy Deposition technique (DED) and its impact on the DSS. It is the DSS that is paramount to the marine industry applications. The study investigated the impact of processing parameters such as hopper rotational speed, laser power, and powder feed rate (PFR) on the quality and integrity of the fabricated objects. By using an Optomec LENS model 150 L-DED system, the study investigates the impact of these variables on microstructure and material properties with an aim to achieve the balance between the production efficiency and the component quality. The experimental results show the relationship between the increase of laser power and the improvement of the sample size and homogeneity with the reduction of the porosity. Extensive examination utilizing light microscopy and X-ray diffraction (XRD), gives us microstructural evolution, which reveals the main role of energy density in controlling the final results of the 3D printed parts. Moreover, the research deals with the incorporation of Composite A and Composite B into the 420SS matrix to represent the duplex stainless-steel conversion, so as to increase tensile strength and corrosion resistance. The results help to find out how process parameters affect DSS, which will eventually lead to the implementation of 3D printing technology in industries.